Development Of Breast Cancer Self-Examination Three Dimensional Simulation - Rahim, Sarni Suhaila; Jamal Akhshah, Nur Aishah; Parumo, Shahril (World Academy of Research in Science and Engineering, 2020)
Breast Cancer Self-Exam: Do It Yourself is developed to teach the community about the steps of breast cancer self-exam. This project simulates about the structure of breast, symptoms of breast cancer and also steps to do breast cancer self-exam. Nowadays, the community really hard to do breast checkup because they are busy with their work and lack of awareness among them. Breast Cancer Self-Exam is really important as a first step to detect the breast cancer. This project produces a 3D animation effect, hence it is a new way to attract the community attention to use this project. There are four modules in this project which are, Module 1-Structure of Normal Breast, Module 2-Steps of Breast Cancer Self-Exam, Module 3-What To Do If Find Lump and lastly Module 4-Statistic of Breast Cancer. In this way, community will more understanding and easy to follow the steps of breast cancer self-exam. It is envisaged that this project will be useful to be used in clinics and hospitals as a new educational material and it can give an awareness to community about how important to do the breast cancer self-exam and prevent it before it is too late.